Political Resonances in the Motets for Saint Louis Under Louis XIV. Issue 2 (3rd July 2021) - Heath, Sean
Abstract : This article examines several motets composed to celebrate Saint Louis (Louis IX) in late seventeenth-century France. As praise of Saint Louis overlapped with that of Louis XIV, these pieces offer insights into the interplay between the French baroque sacred repertoire and royal encomium. In their texts and music, the motets reflect shifts linked not just to the ceremonial contexts for which they were written but also to wider political developments. In particular, the move from ahistorical presentations of a triumphant Louis IX in the 1660s and 1670s to a portrayal of the crusader king's fortitude in captivity and defeat later in the reign reflected the changing context of Louis XIV's wars. By presenting a new view on the political resonances of these works, the article shows the value of sacred music as a source for historians of royal representation under the Sun King.